Differentiation of Candida dubliniensis from Candida albicans on Staib Agar and Caffeic Acid-Ferric Citrate Agar - Al Mosaid, Asmaa (American Society for Microbiology, 2001)
The methods currently available for the identification of the pathogenic yeast Candida dubliniensis all have disadvantages in that they are time-consuming, expensive, and/or, in some cases, unreliable. In a recent study (P. Staib and J. Morschhäuser, Mycoses 42:521–524; 1999) of 14 C. dubliniensis and 11 C. albicans isolates, it was suggested that the ability of C. dubliniensis to produce rough colonies and chlamydospores (chlamydoconidia) on Staib agar (SA) provided a simple means of differentiating it from its close relative C. albicans. In the present investigation, we examined the colony morphology and chlamydospore production of 130 C. dubliniensis and 166 C. albicans isolates on SA and on the related defined medium caffeic acid-ferric citrate agar (CAF). All of the C. dubliniensis and C. albicans isolates produced chlamydospores on the control medium, i.e., rice-agar-Tween agar. However, while none of the C. albicans isolates produced chlamydospores on either SA or CAF, 85.4 and 83.8% of the C. dubliniensis isolates produced chlamydospores on SA and CAF, respectively. All of the C. albicans isolates grew as smooth, shiny colonies on SA after 48 to 72 h of incubation at 30°C, while 97.7% of the C. dubliniensis isolates grew as rough colonies, many (65%) with a hyphal fringe. In contrast, 87.4% of the C. albicans and 93.8% of the C. dubliniensis isolates yielded rough colonies on CAF. Although the results of this study confirm that SA is a good medium for distinguishing between C. dubliniensis and C. albicans, we believe that discrimination between these two species is best achieved on the basis of colony morphology rather than chlamydospore production.